1999
DOI: 10.1192/bjp.174.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Europe

Abstract: Considerable variation occurs in the levels of depression across Europe, the cause for which is not immediately obvious. Case and sub-case levels taken together show greater variability, suggesting that it is not a matter of case/sub-case selection criteria, which were standardised by computer. Substantial levels of depression are shown but 62-82% of persons had no depressive level. Opportunities for treatment exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
20
2
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(37 citation statements)
references
References 30 publications
7
20
2
5
Order By: Relevance
“…This is a first indication of the coexistence of two factors within the EURO-D scale. This finding is also consistent with results from the EUROPED study (Prince et al 1999a, b;Copeland et al 2004) where it was found that, across 14 European centres, these symptoms could be separated into two factors with loss of interest, poor concentration and lack of enjoyment loaded on the first one--called ''motivation''--and depression, tearfulness and wishing to die comprising the second--called ''affective suffering'' or ''depressed affect''. We also use these terms in our study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is a first indication of the coexistence of two factors within the EURO-D scale. This finding is also consistent with results from the EUROPED study (Prince et al 1999a, b;Copeland et al 2004) where it was found that, across 14 European centres, these symptoms could be separated into two factors with loss of interest, poor concentration and lack of enjoyment loaded on the first one--called ''motivation''--and depression, tearfulness and wishing to die comprising the second--called ''affective suffering'' or ''depressed affect''. We also use these terms in our study.…”
Section: Discussionsupporting
confidence: 83%
“…The differentiation between the two components of the EURO-D scale has a strong potential for further exploration. Copeland et al (2004) suggest that while symptoms of depression increase with age, prevalence in later life may be over-diagnosed due to an increase in complaints of lack of interest and motivation which may be affectively neutral and related to cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Women's help-seeking behavior has been described in the literature, where women are reported to be more vulnerable, passive, dependent, and at risk of depression. These findings correspond with those of two large-scale international studies, the EURODEP [28] and the SHARE study [29], which unfortunately did not provide age groupspecific prevalence rates, but suggested that in later life, age and gender are influenced by two factors, affective suffering (including depression, tearfulness, suicidality, sleep problems) and motivational factor (comprising enjoyment, interest, concentration). Women scored higher on the affective suffering factor, while advanced age scored higher on the motivational factor [30].…”
Section: Discussionsupporting
confidence: 65%
“…Depression is a common and burdensome disorder in older individuals (Beekman et al, 1999;Copeland et al, 2004). While the prevalence of major depression (MDD) is relatively low (1.8%), the prevalence of all clinically relevant depressive syndromes, some of which do not fully fulfill criteria for MDD, is high (13.5%) in community dwelling elderly (Beekman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%